Infrastructure Service Quality Analysis in Improving Public Trust in South Sorong District - Sukartono, Anton (KnE Social Sciences, 2025)
This study examines the institutional performance of the Indonesian House of Representatives in carrying out its legislative function with a focus on the 2019-2024 period. Using a qualitative approach with thematic analysis, this study identifies factors that influence the effectiveness of the legislative function and explores the internal and external dynamics that shape the performance of the institution. Data were obtained through in-depth interviews with 25 key informants, documentation studies of 40 legislative products, and direct observation of the discussion process of five strategic bills. The results of the study reveal five main themes that influence the performance of the Indonesian House of Representatives: the complexity of the institutional structure, partisan political dynamics, limited technical capacity and research support, weak substantive public participation, and challenges of inter-institutional coordination. Thematic analysis shows that the complexity of the institutional structure and partisan political dynamics are determinant factors that influence other aspects. This study produces a conceptual model that describes the relationship between themes and their impact on legislative performance. The proposed recommendations include institutional structure reform, strengthening technical capacity, increasing substantive public participation, and improving inter-institutional coordination mechanisms. This study contributes to the development of a legislative institutional performance evaluation model that is contextual to the Indonesian political system and provides recommendations for strengthening institutions to improve the quality of legislation.